Occupational blood and body fluid exposures and human immunodeficiency virus post-exposure prophylaxis amongst intern doctors - Sunday J. Aigbodion; Feroza Motara; Abdullah E. Laher (AOSIS, 2019)
Background: Healthcare workers (HCWs) are constantly vulnerable to occupational blood and body fluid exposures (OBBFEs). Exposed HCWs experience emotional, physical and psychological trauma. Less experienced HCWs, such as intern doctors, are more prone to OBBFEs. Objectives: The aim of this study was to investigate the prevalence and practices pertaining to OBBFEs amongst a select group of intern doctors in the Gauteng province of South Africa. Methods: A quantitative cross-sectional descriptive study using a questionnaire based on a practical model was used. Intern doctors were recruited from four major hospitals in Gauteng. Results: A total of 175 intern doctors participated in the study. There was a total of 182 (mean = 1.04, standard deviation [s.d] 0.88) reported OBBFEs amongst 136 (77.7%) subjects. The exposures occurred predominantly whilst subjects were working in surgery (n = 50, 27.5%), obstetrics and gynaecology (n = 49, 26.9%) and internal medicine (n = 48, 26.4%) departments; were superficial wounds (n = 69, 37.9%); were acquired during vascular puncture or intravenous line insertion (n = 69, 37.9%); and occurred when subjects were working >12 h shifts (n = 101, 55.5%). Human immunodeficiency virus (HIV) post-exposure prophylaxis (PEP) was initiated in 141 (77.5%) out of the 182 exposures. Only 90 (63.8%) subjects completed the recommended 28-day course of PEP. Two (1.1%) subjects reported that they had acquired HIV infection as a consequence of the OBBFE. Conclusion: Occupational blood and body fluid exposures are common amongst intern doctors. It is recommended that regular training, health education and monitoring compliance should be incorporated during the induction of medical intern doctors in hospitals. The availability of PEP regimens with better tolerability will encourage compliance.